Analisis Balance of Interest dalam Studi Kasus Kepentingan Turki Melakukan Kerja Sama dengan Rusia di Suriah pada 2016 – 2019 - Anissa, Andini (Nation State: Journal of International Studies, 2021)
When the Arab Spring swept through the Arab world as far as Syria, Turkey and Russia were not on the same side. Turkey demand a regime change, while Russia supports the regime. The relationship between the two countries was also exacerbated by the downing of the Sukhoi-24 jet which led Russia to impose a number of sanctions on Turkey. However, from 2016 to 2019, the relationship between the two has started to improve. This was marked by various cooperation to end the civil war in Syria. Based on the theory of balance of power, Turkey should balance against Russia because every country always try to prevent one country from dominating. Instead they both cooperate. The military intervention carried out by Russia in Syria in 2015 can be analysed as an attempt to change the global balance of power, while Turkey can be categorized as a regional rising power. This article tries to answer: why Turkey choose to cooperate with Russia in Syria? I argue that the change in the Turkey's foreign policy during the AKP's increasingly harsher against the Kurds. This caused friction with the US, so that Turkey establish strategic relations with Russia to fight Kurdish in Syria.